Insulin-like growth factor 1 promotes neural differentiation of human stem cells from the apical papilla. (November 2021) - Cui, Yujia; Bai, Mingru; Guo, Daimo; Yang, Yueyi; Chen, Haoran; Sun, Jianxun; Xie, Jing; Zhou, Xuedong
Abstract: Objective: Insulin-like growth factor 1 (IGF1) is one of the vital factors in regenerative endodontics. Previous studies have focused on the role of IGF1 in the mineralization of dental tissues. However, the role of IGF1 in the neural differentiation of dental stem cells was little discussed. Design: IGF1 was overexpressed in human stem cells from the apical papilla (hSCAPs) by lentivirus and knocked down in hSCAPs by small interfering RNA. The neural differentiation level of hSCAPs was investigated histologically by HE staining and Nissl staining after neural induction for 3 days. The expression of proteins was examined by western blot and immunofluorescence. Results: IGF1 promoted neural differentiation of hSCAPs, more cell processes and Nissl-positive body stained cells. IGF1 overexpression could both promote glial differentiation in hSCAPs, characterized by the increase of S100β and GFAP proteins, and neuronal differentiation, characterized by the increase of βIII-tubulin and functional GAD67/vGLUT1 proteins. Conversely, IGF1 knockdown suppressed both glial and neuronal differentiation. IGF1 activated AKT to regulate the early neural differentiation of hSCAPs. Conclusions: The results indicate IGF1 could promote neural differentiation of hSCAPs by activating AKT signaling and provide a cue for the candidate of induced neural seeding cells in regenerative endodontics. Highlights: IGF1 promotes hSCAP into stellate-like cell. IGF1 induces neurogenesis of hSCAP. The process is based on AKT signaling.